Pandangan Hukum Islam terhadap Epistemologi Zihar dalam Keluarga - Bakri, Syaiful (Bulletin of Community Engagement, 2024)
The purpose of this paper is to find out the epistemology of zihar in the family is a phenomenon that needs to be understood in the context of Islamic law. Zihar is an Islamic legal term that refers to the statement or action of a husband who considers his wife as a mahram (a relationship that prohibits marriage) for him. In the view of Islamic law, zihar is considered incompatible with the principles of justice, equality and respect that are the cornerstones of husband-wife relationships in Islam. In this journal, the author presents an Islamic legal understanding of zihar and its impact on family relationships. The author also analyzes the Islamic values that underlie husband-wife relationships, including love, compassion, mutual understanding and respect. In the context of Islamic legal views, zihar is considered an act that violates the principles of justice and equality in conjugal relationships. Islam emphasizes the importance of good communication, deliberation, mediation, and fair problem solving in the family. Zihar has no valid legal basis in Islam, and the author emphasizes the need to avoid demeaning and unfair attitudes towards life partners. Keywords: Islamic Law, Epistemology of Zihar, Family